Site-specific fertilizer recommendations for oil palm smallholders using information from large plantations - Webb, M.; Nelson, P.; Rogers, G.; Curry, George (Wiley-VCH, 2011)
Provision of appropriate fertilizer recommendations to smallholder farmers is becoming increasingly important, for reasons of food security, economic viability, and the need to maintain soil fertility. Oil palm is one of the most important crops in the humid tropics, but smallholder growers (< 10 ha) typically have low yields, largely due to inadequate fertilizer inputs and/or incomplete harvesting. It is difficult to produce appropriate fertilizer recommendations for the smallholder growers, due to their large numbers and small farm sizes. In this work, we developed a way of transferring to smallholder growers the fertilizer recommendations that have been developed for nearby plantation fields using large fertilizer trials. The study site was in West New Britain Province, Papua New Guinea, and transfer of information was done using a geographic information system and maps of plantation fields, smallholder blocks, and soil types. The soil-map-unit descriptions were interpreted, and a unified classification system was derived. Then, fertilizer recommendations that had been made on a field-specific basis for the large plantations were allocated to soil types and thereby to individual smallholder blocks. In this way, block-specific fertilizer recommendations were made for more than 4000 individual smallholders. The procedures used were developed into a conceptual framework which is transferable to other regions. Recommendations can be updated as new information becomes available on smallholder block locations or plantation fertilizer recommendations.